2019
DOI: 10.7759/cureus.4338
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pregestational Maternal Sleeping Disorders and Preeclampsia: A Retrospective Cohort Study and Review of the Literature

Abstract: In this retrospective cohort study, primigravidas with normal pregnancies and women who developed preeclampsia (PE) were assigned to complete sleeping disorder questionnaires. The Crown-Rump length (CRL) of the first prenatal screening was used to determine the gestational age and the participants were assigned to complete the following questionnaires according to their everyday life before pregnancy: (1) Pittsburgh Sleep Quality Index (PSQI), (2) Epworth Sleepiness Scale (ESS), and (3) Athens Insomnia Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Five studies investigated the effects of periconceptional sleep problems on hypertensive disorders [ 16 , 20 , 21 , 29 , 33 ]. One cross-sectional study did not find any statistically significant association [ 33 ], whereas longitudinal studies found that poor sleep was associated with more adverse outcomes, although not consistently [ 16 , 20 , 21 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies investigated the effects of periconceptional sleep problems on hypertensive disorders [ 16 , 20 , 21 , 29 , 33 ]. One cross-sectional study did not find any statistically significant association [ 33 ], whereas longitudinal studies found that poor sleep was associated with more adverse outcomes, although not consistently [ 16 , 20 , 21 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Five studies investigated the effects of periconceptional sleep problems on hypertensive disorders [ 16 , 20 , 21 , 29 , 33 ]. One cross-sectional study did not find any statistically significant association [ 33 ], whereas longitudinal studies found that poor sleep was associated with more adverse outcomes, although not consistently [ 16 , 20 , 21 , 29 ]. Haney et al found that diary-assessed sleep latency at 10–12 weeks was associated with systolic blood pressure four weeks later, but this was not statistically significant after correcting for multiple comparisons [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, emerging evidence highlights EDS as an independent pathophysiological entity and a novel indicator of cardiovascular risk [ 41 ]. Several observational studies have suggested a potential association between EDS and HDPs [ 6 , 10 , 42 ]. Our Mendelian randomization analysis further strengthens this evidence by establishing a compelling causal association, highlighting the EDS as a possible preventable risk factor for HDPs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we cannot determine whether the null findings observed between several sleep traits and the risk of HDPs represent objective facts or are a consequence of potential limitations in the statistical power of our study to detect a significant relationship. Although previous observational studies have suggested an association between sleep disorders, such as insomnia [ 9 , 42 ] and short sleep duration [ 3 , 45 ], and increased rates of preeclampsia, it is important to note that the potential impact of residual confounding inherent in the observational setting may hinder the reliability of the drawn conclusions. This is particularly true in the case of preeclampsia, which is known to be influenced by various socioeconomic and behavioral factors [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%